Isolasi dan Karakterisasi Bakteri Asal Sumber Air Panas Non-Vulkanik - Rahmad Lingga; Budi Afriyansyah; Reti Septiani; Ina Miranti (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to isolate and characterize bacteria that live in hot springs on Bangka Island. The research methods used include bacterial isolation; morphological characterization, Gram group determination and biochemical tests; identification; and thermophilic bacteria temperature resistance test. Hot water samples were obtained from 2 locations, namely Pemali Village and Permis Village. The hot water temperature range at both locations is between 38ºC to 52ºC. The results showed that 22 pure isolates were consisting of 9 isolates from Permis Village and 13 isolates from Pemali Village. In conclusion, the characterization results showed that all bacterial isolates were gram-negative bacteria with various biochemical characteristics. Keywords: Thermophilic Bacteria, Non-Volcanic, Bangka Island